TRICHOBEZOAR: A Retrospective Analysis in Hadoti Region - Meena, Dr. Ramgopal; Neniwal, Dr. Vishal Kumar; Meena, Dr. Akhilesh; Singh, Dr. Kshitiz; Khandelwal, Dr. Manish (International Journal of Innovative Research in Medical Science, 2017)
Objective - The surgical removal of a trichobezoar is the rare end complication of the psychiatric disorders trichotillomania and trichophagia. The more severe form of the disease is termed Rapunzel syndrome, where the bezoar extends from the gastric body beyond the pylorus into the duodenum. Most of patients presenting to hospital with symptom of trichobezoar require surgical intervention. Methods - A retrospective review of all cases of trichobezoar at MBS and NMCH hospital, Kota from 2014 to 2016 was performed. Ai m of this study is to analyze demographic data, presenting complaints, imaging, surgical treatment, subsequent management, recurrence and role of psychiatry treatment. Results - All 10 patients were female, ages 12 to 26 years (mean, 18.7 years). Most patients were accurately diagnosed with clinical history, USG abdomen and CECT abdomen. All patients undergone exploratory laparotomy for definitive treatment. At laparotomy, 6 patients were found to have post pyloric extension of the trichobezoar (60%). One case has extension up to terminal part of ileum. There were no other surgical complications or recurrences requiring further exploration. Conclusions - Our series of trichobezoar patients appear to have a high rate of Rapunzel syndrome, and perhaps post pyloric extension should be considered the rule rather than the exception. Our series demonstrates that diagnosis can be established with a thorough history combined with radiography, and treatment should be a combination of laparoscopy and/or laparotomy with psychiatric consultation.